Reverend Dr. Martin Luther King, Jr. March in Downtown Fresno to Saroyan Theatre - Watkins, Howard::::::::: (1985)
?, Carolyn Murphy and Geneva Bennett walking up steps to Saroyan Theatre Plaza Hotel and Conference Center in background